ANALISIS NILAI TAMBAH DAN EFISIENSI TEKNIS AGROINDUSTRI EMPING JAGUNG DI KELURAHAN PANDANWANGI KOTA MALANG - meliana meliana; Dwi Susilowati; Farida Syakir (Program Studi Agribisnis, 2019)
Abstract This study aims to determine how much profit, value added and technical efficiency of corn chips agroindustry. This research was conducted in Pandanwangi Village, Blimbing District, Malang City. Sampling is done by simple random sampling method, as many as 30 producers of corn chips. the analytical method uses R / C Ratio, according to value added (Hayami, et. Al, 1987) and the MLE (maximum likelihood estimation) method frontier production function. The results showed that the R / C ratio was 1.94, then the corn chips agroindustry was worth the effort. The added value obtained is Rp. 11,672.25 and the technical efficiency value is 0.99 so that the agro-industry is said to be technically feasible. Production factors that affect production are corn and labor.Keywords : added value, technical efficiency